The role of artificial intelligence marketing efforts on brand preference mediated by brand experience of TikTok users in DKI Jakarta - Koeswara, Florence Otto; Nugroho, Bernadus Yuliarto (International Journal Labs, 2024)
This study aims to examine the role of Artificial Intelligence (AI) in customer brand preference mediated by brand experience within the context of DKI Jakarta, Indonesia. The study adopted a cross-sectional design, collecting data at a single point in time from August to December 2023. The research focused on TikTok users in DKI Indonesia, targeting individuals aged 18-34 years who had experience using short video platforms like Instagram Reels and YouTube Shorts. For inferential analysis, the study applied Structural Equation Modeling (SEM) using SmartPLS 3.2.9 software. The results showed that brand experience is developed based on the experience of using the services powered by AI technology, thereby shaping brand preference among users. This study found that there is a positive influence between AI marketing efforts on brand experience and brand preference. There are positive influences of brand experience on the brand preference of Tik Tok users. The findings of this study have implications for the companies that specialize in technology and social media, specifically for the Tiktok company.